Keadilan Gender Dalam Keluarga Perspektif Amina Wadud - Muhammad Fadhil; Munawwir Ramadhan (Ahlana: Jurnal Hukum dan Hukum Keluarga Islam, 2026)
This study examines the concept of gender justice in Muslim families through the perspective of Amina Wadud, particularly in the reinterpretation of the concept of qiwamah contained in QS. An-Nisa verse 34. The concept of qiwamah is traditionally often interpreted as the legitimacy of superiority and absolute leadership of men over women in the family structure, which creates a gender hierarchy and places women in a subordinate position. This study uses a normative juridical method with a hermeneutic approach to analyze Amina Wadud's thoughts sourced from her works, especially "Qur'an and Woman" and "Inside the Gender Jihad". The results of the study show that Amina Wadud offers an alternative interpretation of qiwamah as a conditional functional responsibility, not a hierarchy based on gender. In the contemporary socio-economic context where women also play a role in the family economy, qiwamah can be reciprocal or even shifted to women. The implications of Amina Wadud's concept of qiwamah for gender justice in the family include: (1) flexible division of roles between husband and wife according to ability and agreement; (2) participatory decision-making through deliberation without giving veto rights to the husband; (3) firm rejection of domestic violence by interpreting the word "dharaba" as temporary separation from home, not hitting; and (4) equality in rights and obligations based on the principle of reciprocity as stated in QS. Al-Baqarah verse 228